Coexistence Praxis: The Role of Resource Managers in Wolf-Livestock Interactions on Federal Lands - Martin, Jeff Vance; Epstein, Kathleen; Anderson, Robert M.; Charnley, Susan (Frontiers in Conservation Science, 2021)
In resource management, new terms are frequently introduced, reflecting ongoing evolution in the theory and practice of ecology and governance. Yet understandings of what new concepts mean, for whom, and what they imply for management on the ground can vary widely. Coexistence – a prominent concept within the literature and on-the-ground practices around human-wildlife conflict and predator management – is one such term, widely invoked and yet poorly defined. While for some coexistence is the latest paradigm in improving human-wildlife relations, the concept remains debated and indeed even hotly contested by others – particularly on the multiple-use public lands of the American West, where gray wolf conservation, livestock production, and the claims of diverse stakeholders share space. The multiple meanings of coexistence present serious challenges for conservation practice, as what the concept implies or requires can be contested by those most central to its implementation. In this study we examine wolf-livestock management – a classic case of human-wildlife conflict – by focusing on the experiences and perspectives of U.S. Forest Service managers. We conducted a genealogical review exploring coexistence’s multivalence in the literature on human-wildlife conflict, complementing semi-structured interviews conducted with USFS range and wildlife managers on case study forests from across the western states. Through this, we highlight the complexity and multi-dimensionality of the concept and the unique yet under-explored perspective that resource managers bring to these debates. This work draws on insights from political ecology to emphasize the situatedness of manager practice – taking place within a broader set of relations and contextual pressures – while extending political ecologists’ traditional focus on the resource user to a concern with the resource manager as key actor in environmental conflicts. Through our engagement with the experiences and perceptions of USFS managers, who must balance conservation aims with long-established land uses like livestock grazing, we hope to clarify the various dimensions of coexistence and in so doing increase the possibility for collaboration and empathy among managers and stakeholders engaged in this complex socio-ecological challenge.